2004
DOI: 10.1038/sj.jp.7211083
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Combined with Massage Improves Bone Mineralization in Premature Infants: A Randomized Trial

Abstract: A combined massage and physical activity protocol improved bone formation (PICP) but did not affect bone resorption (Pyd). Pyd increased over time in both groups, possibly due to continuous bone resorption and Ca mobilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
1
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 24 publications
2
53
1
6
Order By: Relevance
“…However, some studies have demonstrated that passive exercise for 5 min per day in the first weeks of life promotes greater bone mineralization, Physical therapy for bone mineralization in premature infants CM Vignochi et al using other evaluation methods. [17][18][19][20][21][23][24][25] This study clearly demonstrated that specific motor physical therapy applied 5 times per week for 15 min, over a period of 4 weeks, produced a significant improvement in weight gain, body length, BMC, BMD, LM and BA values measured by total body DEXA when compared to the CG, which did not receive motor physical therapy. Multiple factors influence bone growth and development.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…However, some studies have demonstrated that passive exercise for 5 min per day in the first weeks of life promotes greater bone mineralization, Physical therapy for bone mineralization in premature infants CM Vignochi et al using other evaluation methods. [17][18][19][20][21][23][24][25] This study clearly demonstrated that specific motor physical therapy applied 5 times per week for 15 min, over a period of 4 weeks, produced a significant improvement in weight gain, body length, BMC, BMD, LM and BA values measured by total body DEXA when compared to the CG, which did not receive motor physical therapy. Multiple factors influence bone growth and development.…”
Section: Discussionsupporting
confidence: 51%
“…[10][11][12][13][14][15][16][17] Some researchers have recently suggested that 5 min per day, 5 times per week for 4 weeks of passive exercises with soft compressions result in increased bone mineral density (BMD) in very low birth weight premature infants. [18][19][20][21] This prospective randomized controlled clinical assay was carried out with the objective of evaluating the effects of a motor physical therapy protocol, 15 min per day, 5 days per week, on bone mineralization in very low birth weight preterm infants.…”
Section: Introductionmentioning
confidence: 99%
“…19 Improved bone mineralization and skeletal growth have been associated with programs of daily physical activity in preterm infants. 8,[20][21][22][23] Thus physical activity may improve weight gain through a variety of mechanisms affecting body mass of all typesFadipose, muscle and bone. Additional mechanisms have been proposed that provide a basis for the benefits of massage alone in the promotion of growth.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies have suggested that massage therapy with KS may have positive effects on preterm infants including greater weight gain, [1][2][3][4][5][6][7] improved bone mineralization, 8 earlier hospital discharge, [1][2][3] and more optimal behavioral and motor responses 2-4,9,10 compared to controls. However, there is inconsistency of these findings across studies and methodological concerns with previous trials have led some authors to caution widespread and routine use of preterm infant massage.…”
Section: Introductionmentioning
confidence: 99%
“…202 Massage has been associated with a shift from less total sleep, towards more periods of drowsiness 188 and post-massage sleep may be increased. 193 The use of gentle touch has been associated with lower levels of AS, motor activity and behavioral distress, but no differences were seen in weight gain or behavioral organization.…”
Section: Role Of Sleep In Brain Developmentmentioning
confidence: 99%